Comparison of rheological properties between plastic modified bitumen and normal bitumen - Nazurah Zahidah, Binti Umar Baki (Universiti Malaysia Sarawak, UNIMAS, 2010)
Increasing of the solid waste in Malaysia, the per capita generation from 0.45 to 1.44 kg/day becomes a serious problem. Plastic incineration will not solve the increasing waste problem, but produce other problem such as air pollution. Burning plastics disposal may create dioxin and directly contribute to the depletion of the ozone layer. Since 1995 the plastic recycling programs were introduce in United State. Unfortunately, the recycling of plastic has been proven difficult to be carried out. The biggest problem with plastic recycling is that is difficult to automate the sorting of plastic waste. This study is to determine the rheological properties of modified bitumen. The plastic is used as an additive in the bitumen. In the same time, the solid waste can be reducing. There are three types of test, Rolling Thin Film Oven Test, Penetration Test and Softening Test. From the RTFO test, the mass loss of the unmodified 10% plastic is high. The penetration test, penetration unit is decrease with the increasing of the percentage of the plastic. While in the softening test, the softening point is increasing with the increasing of the percentage of the plastic. From the penetration unit and the vi softening point, the penetration index can be determined. The penetration index is increasing with the increasing of the percentage of plastic. The unmodified bitumen, 1% and 2% of modified bitumen is the conventional paving bitumen type while the 3% to 8% of modified bitumen is blow bitumen type.